Retrospective analysis of bleeding events after central venous catheter placement in thrombotic thrombocytopenic purpura. (June 2021) - Haque, Waqas; Alvarenga, Maria; Vuppala, Suchith; Reddy, Manasa; Sarode, Ravi
Abstract: Background: Thrombotic thrombocytopenic purpura (TTP) is a thrombotic disorder caused by severe deficiency of ADAMTS13. Platelets are transfused prophylactically in non-TTP patients for central venous catheter (CVC) with a count <20 × 10 9 /L to prevent bleeding. However, transfusing platelets in TTP prior to CVC placement remains controversial due to concern for arterial thrombosis and mortality. At our center, platelet transfusion is contraindicated in TTP, therefore, we analyzed data for bleeding complications following CVC placement. Study Design and Methods: 95 acute episodes of TTP were identified. Twenty-six episodes were excluded for insufficient documentation or no CVC placement. The charts of 69 remaining episodes were reviewed. Results: Of 69 TTP episodes, nine (13 %) had bleeding after a CVC placement. Of these, seven bleeds were minor, and the two were major related to the technical issues during femoral venous access causing arterial bleeds. Median platelet count before the CVC placement among those experiencing bleeding complications was 12 × 10 9 /L (range 3–44) as compared to median count of 15 × 10 9 /L (range 4–257) in those who did not bleed (p = 0.258). Among 44 episodes with a platelet count <20 × 10 9 /L, seven (16 %) had bleeds. Conclusion: Major bleeding complications following CVC placement in TTP is uncommon and most likely related to technical challenges. Median platelet count was similar in patients who bled versus those who did not, suggesting that platelet transfusion is unnecessary to correct platelet count prior to a CVC placement in TTP.